2007
DOI: 10.1007/s00114-007-0305-4
|View full text |Cite
|
Sign up to set email alerts
|

Where are the Sunday babies? II. Declining weekend birth rates in Switzerland

Abstract: Birth dates from almost 3 million babies born between 1969 and 2005 in Switzerland were analyzed for the weekday of birth. As in other countries but with unprecedented amplitude, a very marked non-random distribution was discovered with decreasing numbers of births on weekends, reaching -17.9% in 2005. While most of this weekend births avoidance rate is due to fewer births on Sundays (up to -21.7%), the downward trend is primarily a consequence of decreasing births on Saturdays (up to -14.5%). For 2005, these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…The correlation between CS and weekend births avoidance rates for Germany's 16 states further strengthens this result: the higher the CS ratio, the lower the number of weekend births. These data are in good agreement with the observations of parallel increases of CS and weekend births avoidance rates which were shown in other countries as well (Gould et al 2003;Lerchl and Reinhard 2007;Martin et al 2005;Mossialos et al 2005;Signorelli et al 1991). Why should planned births by caesarean sections be scheduled on weekdays?…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The correlation between CS and weekend births avoidance rates for Germany's 16 states further strengthens this result: the higher the CS ratio, the lower the number of weekend births. These data are in good agreement with the observations of parallel increases of CS and weekend births avoidance rates which were shown in other countries as well (Gould et al 2003;Lerchl and Reinhard 2007;Martin et al 2005;Mossialos et al 2005;Signorelli et al 1991). Why should planned births by caesarean sections be scheduled on weekdays?…”
Section: Discussionsupporting
confidence: 81%
“…In fact, some studies provide support for this hypothesis: in California, USA, weekend births avoidance rates paralleled the lower CS ratios during weekends (Gould et al 2003), while at certain hospitals in Italy and Greece the likelihood for CS was higher on weekdays than during the weekend (Mossialos et al 2005;Signorelli et al 1991). For Switzerland, it was also shown that CS ratios and weekend births avoidance rates are significantly correlated (Lerchl and Reinhard 2007). The present study was performed to get additional data for Germany where the 16 German states' data offer the possibility to comparatively analyze the possible associations.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…Births are less likely on weekends (e.g. Goodman et al 2005;Lerchl and Reinhard 2008). Delivering a child outside the normal working week is associated with increased risk of perinatal and neonatal death (e.g.…”
mentioning
confidence: 99%